Pengaruh Penggunaan Aplikasi Kehadiran Mobile (K-Mob) dan Disiplin Pelaksanaan Skema Jam Kerja Terhadap Kinerja Aparatur Sipil Negara (ASN) Pada Bidang Sumber Daya Kesehatan Dinas Kesehatan Provinsi Jawa Barat - Evi Sulistiawati; Abubakar Iskandar; Berliana Kartakusumah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This research aims to evaluate the influence of the use of the Mobile Attendance Application (K-Mob) and discipline in implementing the working hours scheme on the performance of State Civil Apparatus (ASN) in the Health Resources Sector of the West Java Provincial Health Service. This type of research is quantitative research with primary data, where a questionnaire is used as a research instrument. The sample in this study consisted of 23 (twenty three) respondents taken using a saturated sampling technique. The data analysis used was multiple linear regression with SPSS software. The findings from this research show that the use of the Mobile Presence application (K-Mob) influences the performance of the State Civil Apparatus (ASN). Likewise with the discipline in implementing the working hours scheme, which also affects the performance of the State Civil Apparatus (ASN). Furthermore, the research results show that the use of the Mobile Attendance application (K-Mob) and discipline in implementing the working hours scheme simultaneously have an impact on the performance of the State Civil Apparatus (ASN). The implication is that the application of attendance technology and work discipline plays an important role in improving the performance of the State Civil Apparatus (ASN) in the Health Resources Sector of the West Java Provincial Health Service.